ANALYSIS OF SEVERAL FACTORS THAT INFLUENCE THE PRODUCTION VALUE OF THE WOVEN CRAFT INDUSTRY IN GIANYAR REGENCY - Anak Agung Gde Krisyana; I Gusti Wayan Murjana Yasa (Adisam Publisher, 2024)
The industrial sector has a close relationship with production activities, so that building a good industrial situation requires continuous planning and supervision. By paying attention to the determining factors that influence the production process, it will make running an industry easier. The aim of this research is to analyze working capital, labor and technology on the production value of the woven craft industry in Gianyar Regency. This research uses primary data with a quantitative approach obtained from interviews. The population in this study was 65 woven craft industry business units using the entire population as a sample. The sample collection method used was a saturated sample. Data analysis techniques use descriptive statistical analysis, double log regression analysis, Cobb-Douglas production function equation. The results of this research show 1) working capital and labor simultaneously have a significant effect on the production value of the woven craft industry in Gianyar Regency. 2) working capital and labor partially have a positive and significant effect on the production value of the woven craft industry in Gianyar Regency. 3) there is a technological mix of capital and labor on the production value of the woven craft industry in Gianyar Regency. The implication of this research is that the efficiency of production factors plays an important role in an industry, where an industry expects the maximum possible production by spending or using the minimum possible production costs.